1983
DOI: 10.1016/0014-5793(83)81122-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative study of interaction of deacylated tRNA with Escherichia coli ribosomes

Abstract: The 30 S subunit contains 2 sites for tRNA binding (Phe-tRNA, AcPhe-tRNA, tRNA%i with the functional properties of D and A sites of the 70 S ribosome after attachment of 50 S subunit. The third (E) site specific for deacylated tRNA is introduced into 70 S ribosome by its 50 S subunit. The E-site binding of tRNA& is not sensitive to either tetracycline and edeine, and practically codon-independent. The affinity constant of tRNA@ for the E site is 2-3 orders of magnitude lower than that for the D site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
49
1
8

Year Published

1989
1989
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(63 citation statements)
references
References 16 publications
5
49
1
8
Order By: Relevance
“…This location corresponds to the ribosomal E site (exit site), which is the binding site for the uncharged tRNA prior to dissociation from the ribosome, after translocation from the P site (Rheinberger et al, 1981;Grajevskaja et al, 1982;Krillov et al, 1983;Lull et al, 1984). Even though most experimental support for the E site originates from in vitro experiments, tRNA binding to the E site has been implicated in polysomal ribosomes in extracts from growing bacteria, 249…”
Section: Oxford University Pressmentioning
confidence: 99%
“…This location corresponds to the ribosomal E site (exit site), which is the binding site for the uncharged tRNA prior to dissociation from the ribosome, after translocation from the P site (Rheinberger et al, 1981;Grajevskaja et al, 1982;Krillov et al, 1983;Lull et al, 1984). Even though most experimental support for the E site originates from in vitro experiments, tRNA binding to the E site has been implicated in polysomal ribosomes in extracts from growing bacteria, 249…”
Section: Oxford University Pressmentioning
confidence: 99%
“…In the course of translation, tRNA interacts with the ribosome at three different sites+ Prior to formation of a new peptide bond, aminoacyl-and peptidyl-tRNA are positioned in the acceptor (A) and donor (P) sites, respectively+ After peptidyl transfer and translocation, newly deacylated tRNA is transferred to the exit (E) site+ Existence of the E site was realized considerably after the A and P sites were described (Rheinberger et al+, 1981;Grajevskaja et al+, 1982;Kirillov et al+, 1983)+ Significantly less is known about E site location, composition, interaction with tRNA, and function compared to the other two tRNA-binding sites+ Nevertheless, the E site is thought to play an important role in translation+ Binding of tRNA in the E site prior to its release from the ribosome may promote translocation (Lill et al+, 1986(Lill et al+, , 1989 and/or improve accuracy of translation (Geigenmuller & Nierhaus, 1990)+ The critical characteristic of the E site is its strong preference for a deacylated tRNA 39 end (Rheinberger et al+, 1981;Grajevskaja et al+, 1982;Kirillov et al+, 1983;Lill et al+, 1984;Parfenov & Saminsky, 1985)+ Modifications of the 39 terminal tRNA residue or its removal dramatically affect E site binding of tRNA, indicating the importance of the tRNA 39 end for binding in the E site (Lill et al+, 1988)+ The recently deduced X-ray crystallographic structure of the ribosome-tRNA functional complexes showed that in the E site, tRNA contacts the ribosome in three locations: the 39 end and T⌿C loop of tRNA make contacts with the large ribosomal subunit in the cleft between the central protuberance and the L1 stalk, and the anticodon loop interacts with the small subunit between the platform and the head (Cate et al+, 1999)+ Uncharged tRNA bound to the E site of Escherichia coli 70S ribosomes protects from chemical modification a specific set of bases in 23S rRNA, namely, U2111, G2112, G2116, A2169, and C2394 (Moazed & Noller, 1989)+ This evidence suggested a close proximity of tRNA to rRNA in the E site+ From this, and from the observation that modifications of the 39 terminal adenine of tRNA decreased tRNA binding to the E site, a base pairing between the 39 terminal A of tRNA and U2111 of 23S rRNA was proposed (Lill et al+, 1988)+ However, tRNA-protein interactions can contribute to tRNA binding in the E site as well+ tRNA probes carrying 2-azidoadenosine near their 39 ends could be crosslinked to the protein L33 in the ribosomal E site, suggesting that L33 may facilitate tRNA binding (Wower et al+, 1993)+ At the same time, the anticodon loop of the E site-bound tRNA was crosslinked to protein S11 and 16S rRNA, revealing the contacts between the tRNA anticodon arm and the small ribosomal subunit+ Consensus has not yet been reached on the extent of contribution of codon-anticodon interaction to the tRNA binding in the E site …”
Section: Introductionmentioning
confidence: 99%
“…There are two tRNA-binding sites on the 30S subunits (21). location to that of native tRNA, the assay was altered to measure the ability of each unlabeled tRNAPhe domain to compete with 5'-32P-labeled native tRNAPhe for programmed 30S ribosomal subunits.…”
mentioning
confidence: 99%
“…The tricylic Y's inability to base pair facilitates the open-loop conformation (6); its increased hydrophobic character, as compared with G. is important to an improved base stacking ofthe anticodon (32). Since there are two tRNA-binding sites on 30S ribosomal subunits (21), the affinity of tRNAPhle to the two sites on the ribosome are probably differentially affected by modification and ion binding. To determine if anticodon loop modifications were important to the ribosome binding of other tRNAs, we screened the 507 reported tRNA sequences (European Molecular Biology Laboratory, tRNA sequence data bank, Heidelberg) for their potential to form WatsonCrick base pairs across the anticodon loop.…”
mentioning
confidence: 99%